The politics of scale in policy : scalecraft and education governance - Papanastasiou, Natalie (Policy Press, 2019)
Drawing on empirical data from the field of education governance, the book traces how scales are crafted and mobilised in policymaking practices, demonstrating that 'scalecraft' is key to understanding the production of hegemony.